New Literacies: Some Implications for Language Teachers - Harendita, Monica Ella (LLT Journal: A Journal on Language and Language Teaching, 2014)
The ever-changing development of digital technology has become a scapegoat that exacerbates literacy. In scrutinising this issue, this article counters the simplistic view on literacy. Instead, it views literacy as socially, culturally and historically constructed. Therefore, the traditional definition of literacy, which is the ability to read and write, may not fit the digital age. This article discusses how digital technologies have reshaped the nature of literacy. After discussing literacy, and the Internet in general and Web 2.0 in particular, this paper presents some implications for language teachers in dealing with the altered literacy practices. First, critical literacy should be embedded in classroom practices so as to make students critically evaluate the free-flowing information on the Internet. Second, language teachers should nurture participatory culture of the students by encouraging collaboration among them.